Câmara de prevenção e resolução administrativa de conflitos do estado do Tocantins: diretrizes contributivas para a sua instalação e o seu funcionamento - Centeno, Murilo Francisco (Universidade Federal do Tocantins, 2017)
This paper discusses the alternative means of conflict resolution in Public Administration. Therefore, the purpose of the dissertation was to propose contributory guidelines for the institution and operation of the Chamber of Prevention and Administrative Resolution of Conflicts of the State of Tocantins, to be implemented in compliance with the provisions of article 174 of the Code of Civil Procedure of 2015 and article 32 of Law of Mediation, considering that the legislative set delineated the fundamental features of the congeners chambers, to be created within the scope of the Public Administrations, referring, however, to the federative entities, the regulation of the way of composition, functioning and other specificities. The scarcity of objective parameters of regulations challenges Public Administrations to make the aforementioned chambers effective. Thus, through an eminently bibliographical and documentary research, the theoretical foundations underlying the use of consensuality mechanisms within the Public Administration were investigated, especially from the administrative consensuality expressed in the dialogical or democratic public administration, qualified by the participation of the administered in the formation of the Administrative will , as well as manifested in the increment of the contractual activity and management of agreements, which included the alternative means of conflict resolution involving the Public Administration. The viability and legal possibility of negotiation in the prevention and resolution of conflicts involving public administration entities were discussed through the explosion of the arguments that grounded the objections to the transaction in the controversies of this nature, therefore the principiology and principles guiding that oriented the Legislation mention before were also studied. The Chamber of Conciliation and Arbitration of the Federal Administration, linked to the Federal Attorney General's Office, was also investigated, considering that the Union's experience in the extrajudicial and consensual management of its own conflicts inspires legal provisions. From this path and the critical analysis of the concrete experience of the Union, it was presented contributory guidelines for the establishment and functioning of the local chamber, linked to the Attorney General's Office.